Optimizing Nanostore Performance in Honduras: Interplay of Total Quality Management, Adaptability, and Reconfigurability - Ortega-Jimenez, Cesar H.; Amador Matute, Andrea Michelle; Cruz Amaya, Jennifer Daniela; Melgar-Martínez, Narciso Antonio (LACCEI, 2024)
This study presents a theoretical model rooted in Resource Theory and Contingency Theory, examining the integration of Total Quality Management (TQM) and reconfigurability with adaptability and performance in nanostores. With responses from 143 nanostore owners, regression analysis supports two key findings: (i) higher TQM implementation increases the likelihood of nanostores adopting adaptability as an operational strategy; (ii) reconfigurability moderates the relationship between TQM levels and adaptability implementation, contributing to enhanced efficiency. Incorporating resource-based theory, the study explores the role of TQM and reconfigurability in achieving performance through adaptability. Practical guidance for practitioners and nanostore owners seeking improved performance through adaptability is provided, along with proposed avenues for future research.